Introduction - Jacqueline Glomski (Universitat de Girona; Universitat Autònoma de Barcelona, 2016)
John Barclay’s Argenis (1621) is a Neo-Latin political romance that tells the story of the chaste passion of the only daughter of the king of Sicily for a foreign nobleman to whom she is secretly betrothed. It was one of the most widely read and imitated novels of the seventeenth century, with numerous prose translations, abridgements, and sequels in all the major languages of Europe. Although a great novel does not necessarily make a great play, Barclay’s story also had authentic dramatic potential, and it was adapted for the stage five times, in French (twice), Spanish, German, and Italian, from the 1620s to the end of the century. This essay introduces the main features of Barclay’s work, sketches its literary and political context, and suggests reasons why Barclay’s stimulating combination of politics and romance was so attractive to the three playwrights discussed in this cluster: Pierre Du Ryer, Pedro Calderón de la Barca, and Christian Weise.